Humoral response to John Cunningham virus during pregnancy in multiple sclerosis - M. Saraste; S. Atula; K. Hedman; S. Hurme; A. Jalkanen; M. Sneck; H.-M. Surcel; A.H. Maghzi; L. Airas (Elsevier B.V., 2022)
Conclusions
JCV-Ab levels remain unaltered during MS pregnancy, while the total IgG concentration is reduced/diluted due to increasing plasma volumes during the course of pregnancy. This may imply a biologically significant alteration in the immune response to JCV during MS pregnancy.